Isolation and Identification of Chemical Constituents from Zhideke Granules by Ultra-Performance Liquid Chromatography Coupled with Mass Spectrometry - Guangqiang Huang; Jie Liang; Xiaosi Chen; Jing Lin; Jinyu Wei; Dongfang Huang; Yushan Zhou; Zhengyi Sun; Lichun Zhao (Journal of Analytical Methods in Chemistry)
Chemical constituents from Zhideke granules were rapidly isolated and identified by ultra-performance liquid chromatography (UPLC) coupled with hybrid quadrupole-orbitrap mass spectrometry (MS) in positive and negative ion modes using both full scan and two-stage threshold-triggered mass modes. The secondary fragment ion information of the target compound was selected and compared with the compound reported in databases and related literatures to further confirm the possible compounds. A total of 47 chemical constituents were identified from the ethyl acetate extract of Zhideke granules, including 21 flavonoids and glycosides, 9 organic acids, 4 volatile components, 3 nitrogen-containing compounds, and 10 other compounds according to the fragmentation patterns, relevant literature, and MS data. The result provides a new method for the analysis of chemical constituents of Zhideke granules which laid the foundation for quality control and the study of pharmacodynamic materials of Zhideke granules.